Various non-chemical control methods: their effectiveness on blister blight disease (Exobasidium vexans Massee) on tea - Rayati, Dini Jamia (Research Institute for Tea and Cinchona, 2011)
Chemical control method of blister blight disease (Exobasidium vexans Massee) on tea could inflict various negative impacts. In order to obtain an environmentally sound control method of blister blight disease, a field trial has been conducted to know the effectiveness of various non-chemical control methods on blister blight disease. The trial was carried out at Ciliwung Tea Plantation (1.400 m asl), Bogor, West Java, designed in a randomized complete block, with eight treatments and three replications. The treatments tested comprised: the application of an antagonistic fungus (Verticillium sp.) on two level of doses, 2 and 3 kg/ha; the application of nutrient (mollases 2% + urea 1%); the application of the combination of the antagonistic fungus and nutrient (Verticillium sp. 2 kg/ha + mollases 2% + urea 1%); the application of compost tea with and without aeration system; the application of copper-chemical fungicide as standard treatment; and control. All of the treatments were applied by spraying on tea bushes infected by blister blight disease, and the parameter observed was blister blight disease intensity, which was formulated in percentage of disease intensity index (DII). The results showed that in heavy-attack condition (DII higher than 50%), only the treatments of compost tea application which were effective in suppressing the intensity of blister blight disease. Meanwhile, other treatments of non-chemical control methods could not suppress the disease intensity, even the copper-chemical fungicide as a standard treatment was no longer effective too.Â The results also showed that the use of aeration system in making compost tea could increase the effectiveness of compost tea in controlling blister blight disease. The effectiveness level of aerated compost tea (42.9%) was higher than non-aerated compost tea (29.5%).